ONBOARD EQUIPMENT FOR RNAV (Perner's Contacts, 2011)
This article describes basic principles of area navigation (RNAV) and their benefits in airspace management utilization. Furthermore it focuses on onboard equipage used for this type of navigation. In the article's conclusion two dimensional, three dimensional and four dimensional RNAV systems are mentioned.
Keywords: Area navigation; onboard equipment; RNAV